Effects of sliding amplitude and normal load on the fretting wear behavior of alloy 690 tube exposed to high temperature water. (December 2017) - Guo, Xianglong; Lai, Ping; Tang, Lichen; Wang, Jiamei; Zhang, Lefu
Abstract: The effects of sliding amplitude and normal load on the fretting wear behavior of alloy 690 tube exposed to an environment simulating the secondary side water chemistry of nuclear power plant are studied and the fretting wear process is discussed. The results indicate that with the increase of sliding amplitude and normal load, the wear volume of the alloy 690 tube is increasing, however, the wear coefficient firstly decreases then becomes relatively constant. This is because that the wear mode of the materials is changed from abrasive wear to delamination wear with the increase of sliding amplitude and normal load. The synergic effects of corrosion and mechanical wear on fretting wear behavior of the alloy 690 tube are also discussed and a model is proposed to qualitatively reveal the fretting wear process of the alloy 690 tube. Highlights: When exposed to 285℃ water, the sliding amplitude and normal load determines the wear mode of the 690 alloy, which changes from abrasive wear to delamination wear with the increase of sliding amplitude and normal load. The synergic effect of corrosion and mechanical wear on fretting wear behavior of the alloy 690 tube has been qualitatively modelled.